EARLY COMPLICATIONS OF ELECTIVE AND EMERGENCY TRACHEOSTOMY - Muhammad, Raza; Khan, Farida; Rehman, Fazal; Iqbal, Johar; Khan, Munib; Ullah, Gohar (Journal of Ayub Medical College Abbottabad, 2012)
Background: Tracheostomy is a life saving procedure when it is performed for an appropriate indication and surgical technique. The aim of this study was to compare the early complications of elective and emergency tracheostomy in our setup. Methods: This comparative study was conducted at the ENT Department, Hayatabad Medical Complex (HMC) from March 2009 to March 2010. A total of 100 patients included in this study were divided in to two equal groups, group A undergoing elective tracheostomy and group B undergoing emergency tracheostomy. The results of hundred patients were compared and analysed from stand point of age, sex, disease pattern, operative procedure and postoperative complications associated with tracheostomy. Results: A total of 100 patients were included with age ranging from 17 to 88 years. The average age was 35 years in elective cases and was 32 years in emergency cases. The male to female ratio was 2.9:1 in elective cases and 4.6:1 in emergency cases. The overall complications rates were 38% in elective cases and 56% in emergency cases. Conclusion: Early complications of emergency tracheostomy are more common than elective tracheostomy. Keywords: Tracheostomy, complications